2018
DOI: 10.1002/jmor.20834
|View full text |Cite
|
Sign up to set email alerts
|

Are there general laws for digit evolution in squamates? The loss and re‐evolution of digits in a clade of fossorial lizards (Brachymeles, Scincinae)

Abstract: Evolutionary simplification of autopodial structures is a major theme in studies of body-form evolution. Previous studies on amniotes have supported Morse's law, that is, that the first digit reduced is Digit I, followed by Digit V. Furthermore, the question of reversibility for evolutionary digit loss and its implications for "Dollo's law" remains controversial. Here, we provide an analysis of limb and digit evolution for the skink genus Brachymeles. Employing phylogenetic, morphological, osteological, and my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 85 publications
2
35
0
Order By: Relevance
“…These taxa are relatively long-branched (see Daza et al [2012] with regard to the first two of these) and further investigation is needed. In studies in which the actual structure of purported re-evolved features have been examined (e.g., Ober 2003;Kohlsdorf and Wagner 2006;Wagner et al 2018), anatomical differences have been noted compared with the original condition. Re-evolution of entire structural complexes in their exact original configuration is generally considered unlikely (Kearney and Stuart 2004;Goldberg and Igić 2008;Wake et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These taxa are relatively long-branched (see Daza et al [2012] with regard to the first two of these) and further investigation is needed. In studies in which the actual structure of purported re-evolved features have been examined (e.g., Ober 2003;Kohlsdorf and Wagner 2006;Wagner et al 2018), anatomical differences have been noted compared with the original condition. Re-evolution of entire structural complexes in their exact original configuration is generally considered unlikely (Kearney and Stuart 2004;Goldberg and Igić 2008;Wake et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These reptiles display a vast diversity of life history traits, particularly in dietary habits and reproductive modes (Shine and Bonnet, 2000;Vitt and Caldwell, 2013). They have also played an important role in addressing many higher-level questions in ecology and evolutionary biology across numerous fields of study that include using venom to study evolutionary key innovations (Casewell et al, 2013;Sunagar et al, 2016;Calvete, 2017) and studies of phenotypic evolution (Wagner et al, 2018;Watanabe et al, 2019), reproductive mode (Blackburn, 2006;Pyron and Burbrink, 2014), and adaptive radiation (Losos and Miles, 2002). Despite such a rich history of foundational research on the group, microbiome evolution among squamate reptiles remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Within skinks, the genus Brachymeles presents a particularly interesting case for investigating the evolution of the body axis, as members of the clade display a spectrum of body sizes and degree of elongation, as well as reduction of limbs and limb anatomical elements (Siler & Brown, 2011). This group of 41 species is largely endemic to the Philippines and shows notable variation in size, with a more than four‐fold difference in body length among species (Uetz, Freed, & Hošek, 2019; Wagner et al, 2018). Previous research on Brachymeles has revealed that species with reduced or absent limbs tend to have longer, slimmer bodies with more presacral vertebrae, while species with longer limbs have shorter, fatter bodies with fewer presacral vertebrae (Bergmann & Moringa, 2019; Greer, Caputo, Lanza, & Palmieri, 1998; Siler & Brown, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The complex nature of the body axis suggests that a more holistic 3D‐modeling approach would allow consideration of how cross‐sectional areas and circumference scale with size. We focus on the body axis, and not on the degree of limb development, which was addressed in Siler and Brown (2011) and Wagner et al (2018).…”
Section: Introductionmentioning
confidence: 99%